The Prevention of Spontaneous Combustion in south Nottinghamshire - T. F. Bamber (The Institute of Materials, Minerals and Mining, 1905)
The South Nottinghamshire Area has not been greatly troubled by spontaneous combustion until the last few years, during which the Blackshale Seam has been developed and exploited. The problem was first encountered at a colliery which was heavily preoccupied with a major reconstruction scheme, and with the sudden appearance of a completely new hazard both men and management had to adapt themselves very quickly to meet the situation. The paper contributed to the Symposium by the South Nottinghamshire Area illustrates the problems by reference to actual incidents, and shows how the lessons learned from them have been applied to the shaping of future policy on the avoidance and treatment of spontaneous combustion.